APPLICATION OF GREEDY ALGORITHM IN FINDING THE SHORTEST PATH TO HAJI ADAM MALIK CENTRAL GENERAL HOSPITAL MEDAN - Arista Widya, Syipa (Pena Cendekia Insani, 2023)
This research aims to simplify access to Haji Adam Malik Medan Central General Hospital by using the Greedy algorithm efficiently. With various alternative routes available, the Greedy algorithm is applied to determine the shortest path that minimizes travel time. Data was obtained via Google Maps from four reference points: Belawan, Aceh, Berastagi, and Kualanamu Airport. The results reveal that the optimal route from Belawan is Node A ? a1 ? a3 ? R, covering 37 km in 55 minutes. From Aceh, the best path is Node B ? a1 ? a3 ? R, with a distance of 137 km in 1 hour 19 minutes. For Berastagi, the fastest route is C ? R, with a distance of 53 km and a travel time of 1 hour 31 minutes. From Kualanamu Airport, the optimal path is Node D ? a4 ? a2 ? R, covering 46 km in 1 hour 3 minutes. This study demonstrates the Greedy algorithm’s effectiveness in solving shortest path optimization problems and highlights its potential to serve as a foundation for navigation system development in Medan. It provides practical solutions for improving travel efficiency to critical locations like hospitals.